Aerogel reinforced basalt fiber and glass fiber composite fire-resistant material for bridge and preparation method of aerogel reinforced basalt fiber and glass fiber composite fire-resistant material

By combining basalt fibers and glass fibers with silica aerogel, bridge fire-resistant materials with high stability and low thermal conductivity are prepared, which solves the problem of poor stability of existing materials in high temperature environments, and achieves the effect of reducing costs and improving fire-resistant performance.

CN119528541APending Publication Date: 2025-02-28NANJING SECOND YANGTZE RIVER BRIDGE CO LTD +3
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411573666.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing bridge fire-resistant materials have poor stability in high temperature environments, making it difficult to effectively reduce the thermal conductivity, resulting in frequent bridge fire accidents.

Method used

The preparation method of aerogel-reinforced basalt fiber and glass fiber composite materials is adopted, and the basalt fiber and glass fiber are combined with silica aerogel to form a composite material with high stability and low thermal conductivity.

Benefits of technology

The effect of reducing material costs while ensuring high stability and low thermal conductivity is achieved, and the fire resistance of bridges is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528541A_ABST
    Figure CN119528541A_ABST
Patent Text Reader

Abstract

The invention discloses an aerogel reinforced basalt fiber and glass fiber composite fire-resistant material for bridges and a preparation method thereof. The preparation method comprises the following steps: (1) cutting basalt fibers and glass fibers into short fibers, and opening and pressing the short fibers into a basalt fiber and glass fiber composite fibrofelt; (2) mixing tetraethoxysilane, ethanol and water according to a certain proportion to prepare silica sol; and (3) mixing the basalt fiber and glass fiber composite fiber felt with the silicon dioxide sol to obtain the silicon dioxide aerogel, basalt fiber and glass fiber composite material. By combining the advantages of high stability of the basalt fibers and low heat conductivity coefficient of the glass fibers, the basalt fibers and the glass fibers are combined to prepare the composite fiber felt, and the composite fiber felt and the silicon dioxide aerogel are further compounded; therefore, the aerogel reinforced basalt fiber and glass fiber composite material with high stability and low heat conductivity coefficient is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fire-resistant materials, and in particular to an aerogel-reinforced basalt fiber and glass fiber composite fire-resistant material for bridges and a preparation method thereof. Background Art

[0002] With the rapid development of my country's economy, the traffic volume on bridges, especially the traffic volume of hazardous chemicals vehicles, has increased significantly, resulting in a large number of bridge fire accidents. Fires can cause irreparable damage to bridges and even cause bridge collapse, resulting in major safety accidents and economic losses. Therefore, it is necessary to vigorously develop refractory materials suitable for the specific application environment of bridges, which is of great practical significance to the healthy and stable development of my country's bridge fire safety and economic construction. Silica aerogel is a porous material with a porosity of more than 90% and extremely low thermal conductivity. Selecting suitable refractory fibers and silica aerogel composites can effectively reduce the thermal conductivity of refractory fibers.

[0003] Basalt fiber is a natural high-temperature refractory material. It is made of natural basalt ore through melt spinning and stretching. It has the characteristics of high melting point, excellent high temperature resistance, acid and alkali resistance, resistance to biological erosion and good mechanical properties. This material can work stably for a long time in a high temperature environment and is not easily damaged by heat. Glass fiber has a lower thermal conductivity, but it cannot work at high temperatures for a long time and has poor stability. Summary of the invention

[0004] In order to make up for this shortcoming, the purpose of the present invention is to provide a method for preparing aerogel reinforced basalt fiber and glass fiber composite fire-resistant material for bridges, which can greatly reduce the cost while combining the extremely low thermal conductivity of silica aerogel with the high melting point and high strength of basalt fiber and glass fiber.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing an aerogel-reinforced basalt fiber and glass fiber composite fire-resistant material for bridges, comprising the following steps:

[0007] (1) Preparation of basalt fiber and glass fiber composite fiber felt:

[0008] Firstly, basalt fiber and glass fiber are used as raw materials, and the basalt fiber and glass fiber are cut into short fibers;

[0009] Then, the short-fiber basalt fiber and the glass fiber are mixed, and the mixed fiber is pretreated, and then the mixed fiber is moved into a drum dryer to dry the mixed fiber and obtain a uniformly mixed mixed fiber;

[0010] Finally, the mixed fibers are opened by an opening machine, and then put into a carding machine for fiber combing, and then needle-punched and compacted to obtain a basalt fiber and glass fiber composite fiber mat;

[0011] (2) Preparation of silica sol:

[0012] Firstly, tetraethoxysilane, ethanol and water are mixed to prepare a silicon precursor solution;

[0013] The pH value of the silicon precursor solution is then adjusted with hydrochloric acid;

[0014] Finally, the mixture of hydrochloric acid and silicon precursor solution is stirred and heated to obtain silica sol;

[0015] (3) Preparation of aerogel reinforced basalt fiber and glass fiber composites:

[0016] First, the basalt fiber and glass fiber composite fiber felt prepared in step (1) are immersed in the silica sol prepared in step (2) and placed in a vacuum box;

[0017] Then, the product is taken out from the vacuum box and the pH value is adjusted with ammonia water to promote the gelation of the silica sol to form a composite gel. After the composite gel is formed, it is placed in ethanol for aging;

[0018] Then, the water in the composite gel is replaced with n-hexane, and the composite gel is placed in a modification solution for a one-step modification;

[0019] Finally, the modified composite gel was pre-frozen and then vacuum freeze-dried for 48 hours to obtain a composite material of silica aerogel, basalt fiber and glass fiber.

[0020] Furthermore, in step (1), the length of the short fibers is 18-22 mm, and the weight ratio of the short fiber-shaped basalt fibers to the glass fibers is 100-65:0-35.

[0021] Furthermore, in step (1), the pretreatment is to use industrial alcohol as a cleaning agent to stir and clean the mixed fibers.

[0022] Furthermore, in step (2), tetraethoxysilane, ethanol and water are mixed in a molar ratio of 0.4-0.6:7-9:2.5-3.5.

[0023] Furthermore, in step (2), the pH value of the silicon precursor solution is adjusted to 3-4 with 0.3-0.5 mol / L hydrochloric acid; the mixture of hydrochloric acid and silicon precursor solution is stirred at 38-42° C. and heated for 2 h to obtain silica sol.

[0024] Furthermore, in step (3), after the product is taken out from the vacuum box, the pH value is adjusted to 6-7 with 0.4-0.6 mol / L ammonia water.

[0025] Further, in step (3), the modified solution is composed of hexamethyldisilazane and n-hexane in a molar ratio of 0.8-1.2:3-5.

[0026] Furthermore, in step (3), liquid nitrogen is used for a pre-freezing operation for 4 hours, and the pre-cooled composite gel is vacuum freeze-dried at -60 to -50°C for 48 hours to obtain a composite material of silica aerogel, basalt fiber and glass fiber.

[0027] Furthermore, in step (3), after the composite gel is formed, it is placed in ethanol at 38-42° C. for aging for 12 hours.

[0028] The present invention also provides an aerogel-reinforced basalt fiber and glass fiber composite fire-resistant material for bridges prepared by the method.

[0029] The advantages of the present invention over the prior art are as follows: the present invention combines the advantages of high stability of basalt fiber and low thermal conductivity of glass fiber, combines basalt fiber with glass fiber to prepare composite fiber felt, and further compounds the composite fiber felt with silica aerogel, thereby preparing an aerogel-reinforced basalt fiber and glass fiber composite material with both high stability and low thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The above and other objects and features of the present disclosure will become apparent by describing in detail embodiments of the present disclosure with reference to the accompanying drawings.

[0031] Figure 1 Actual picture of the prepared aerogel reinforced basalt fiber and glass fiber composite materials.

[0032] Figure 2 The thermal conductivity of the prepared aerogel reinforced basalt fiber and glass fiber composites.

[0033] Figure 3 This is the temperature rise curve of the fire resistance test of the composite material prepared in Example 1.

[0034] Figure 4 This is the temperature rise curve of the fire resistance test of the composite material prepared in Example 2.

[0035] Figure 5 This is the temperature rise curve of the fire resistance test of the composite material prepared in Example 3. DETAILED DESCRIPTION

[0036] The present invention is further described below through specific embodiments. It should be pointed out that, for ordinary technicians in this field, several modifications and improvements can be made without departing from the principle of the present invention, and these should also be regarded as belonging to the protection scope of the present invention.

[0037] The contents not described in detail in the specification of the present invention belong to the common knowledge of the professionals in this field.

[0038] Embodiment 1:

[0039] A method for preparing an aerogel-reinforced basalt fiber and glass fiber composite fire-resistant material for bridges, comprising the following steps:

[0040] (1) Preparation of basalt fiber and glass fiber composite fiber felt:

[0041] Firstly, basalt fiber and glass fiber are used as raw materials, and the basalt fiber and glass fiber are cut into 20mm short fibers;

[0042] Then, short-fiber basalt fiber and glass fiber are weighed in a ratio of 85:15, and the weighed mixed fiber is added into a container containing industrial alcohol for stirring and washing, and then moved into a drum dryer to dry and mix the mixed fiber to obtain a uniform mixed fiber;

[0043] Finally, the mixed fibers were opened by an opening machine, and then put into a carding machine for fiber combing. After needle punching and compaction, a 10mm thick basalt fiber and glass fiber composite fiber mat was obtained.

[0044] (2) Preparation of silica sol:

[0045] First, tetraethoxysilane, ethanol and water are mixed in a molar ratio of 0.5:8:3 to prepare a silicon precursor solution;

[0046] Then, the pH of the silicon precursor solution was adjusted to 3.5 with 0.4 mol / L hydrochloric acid;

[0047] Finally, the mixture of hydrochloric acid and silicon precursor solution was stirred at 40°C and heated for 2 h to obtain silica sol;

[0048] (3) Preparation of aerogel reinforced basalt fiber and glass fiber composites:

[0049] First, the basalt fiber and glass fiber composite fiber felt prepared in step (1) are immersed in the silica sol prepared in step (2) and placed in a vacuum box, and the time for the silica sol to infiltrate the composite fiber is controlled to be 2 hours;

[0050] Then, the product was taken out of the vacuum box and the pH was adjusted to 6.5 with 0.5 mol / L ammonia water to promote the gelation of the silica sol to form a composite gel. After the composite gel was formed, it was placed in ethanol at 40° C. and aged for 12 hours;

[0051] Then, the water in the composite gel is replaced with n-hexane, and the composite gel is placed in a modification solution for a one-step modification, wherein the modification solution is composed of hexamethyldisilazane and n-hexane in a molar ratio of 1:4;

[0052] Finally, the modified composite gel was pre-frozen for 4 hours and then vacuum freeze-dried at -55°C for 48 hours to obtain a composite material of silica aerogel, basalt fiber and glass fiber, namely, an aerogel-reinforced basalt fiber and glass fiber composite material.

[0053] Embodiment 2:

[0054] A method for preparing an aerogel-reinforced basalt fiber and glass fiber composite fire-resistant material for bridges, comprising the following steps:

[0055] (1) Preparation of basalt fiber and glass fiber composite fiber felt:

[0056] Firstly, basalt fiber and glass fiber are used as raw materials, and the basalt fiber and glass fiber are cut into 20mm short fibers;

[0057] Then, short-fiber basalt fiber and glass fiber are weighed in a ratio of 75:25, and the weighed mixed fiber is added into a container containing industrial alcohol for stirring and washing, and then moved into a drum dryer to dry and mix the mixed fiber to obtain a uniform mixed fiber;

[0058] Finally, the mixed fibers were opened by an opening machine, and then put into a carding machine for fiber combing. After needle punching and compaction, a 10mm thick basalt fiber and glass fiber composite fiber mat was obtained.

[0059] (2) Preparation of silica sol:

[0060] First, tetraethoxysilane, ethanol and water are mixed in a molar ratio of 0.5:8:3 to prepare a silicon precursor solution;

[0061] Then, the pH of the silicon precursor solution was adjusted to 3.5 with 0.4 mol / L hydrochloric acid;

[0062] Finally, the mixture of hydrochloric acid and silicon precursor solution was stirred at 40°C and heated for 2 h to obtain silica sol;

[0063] (3) Preparation of aerogel reinforced basalt fiber and glass fiber composites:

[0064] First, the basalt fiber and glass fiber composite fiber felt prepared in step (1) are immersed in the silica sol prepared in step (2) and placed in a vacuum box, and the time for the silica sol to infiltrate the composite fiber is controlled to be 2 hours;

[0065] Then, the product was taken out of the vacuum box and the pH was adjusted to 6.5 with 0.5 mol / L ammonia water to promote the gelation of the silica sol to form a composite gel. After the composite gel was formed, it was placed in ethanol at 40° C. and aged for 12 hours;

[0066] Then, the water in the composite gel is replaced with n-hexane, and the composite gel is placed in a modification solution for a one-step modification, wherein the modification solution is composed of hexamethyldisilazane and n-hexane in a molar ratio of 1:4;

[0067] Finally, the modified composite gel was pre-frozen for 4 hours and then vacuum freeze-dried at -55°C for 48 hours to obtain a composite material of silica aerogel, basalt fiber and glass fiber, namely, an aerogel-reinforced basalt fiber and glass fiber composite material.

[0068] Embodiment 3:

[0069] A method for preparing an aerogel-reinforced basalt fiber and glass fiber composite fire-resistant material for bridges, comprising the following steps:

[0070] (1) Preparation of basalt fiber and glass fiber composite fiber felt:

[0071] Firstly, basalt fiber and glass fiber are used as raw materials, and the basalt fiber and glass fiber are cut into 20mm short fibers;

[0072] Then, short-fiber basalt fiber and glass fiber are weighed in a ratio of 65:35, and the weighed mixed fiber is added into a container containing industrial alcohol for stirring and washing, and then moved into a drum dryer to dry and mix the mixed fiber to obtain a uniform mixed fiber;

[0073] Finally, the mixed fibers were opened by an opening machine, and then put into a carding machine for fiber combing. After needle punching and compaction, a 10mm thick basalt fiber and glass fiber composite fiber mat was obtained.

[0074] (2) Preparation of silica sol:

[0075] First, tetraethoxysilane, ethanol and water are mixed in a molar ratio of 0.5:8:3 to prepare a silicon precursor solution;

[0076] Then, the pH of the silicon precursor solution was adjusted to 3.5 with 0.4 mol / L hydrochloric acid;

[0077] Finally, the mixture of hydrochloric acid and silicon precursor solution was stirred at 40°C and heated for 2 h to obtain silica sol;

[0078] (3) Preparation of aerogel reinforced basalt fiber and glass fiber composites:

[0079] First, the basalt fiber and glass fiber composite fiber felt prepared in step (1) are immersed in the silica sol prepared in step (2) and placed in a vacuum box, and the time for the silica sol to infiltrate the composite fiber is controlled to be 2 hours;

[0080] Then, the product was taken out of the vacuum box and the pH was adjusted to 6.5 with 0.5 mol / L ammonia water to promote the gelation of the silica sol to form a composite gel. After the composite gel was formed, it was placed in ethanol at 40° C. and aged for 12 hours;

[0081] Then, the water in the composite gel is replaced with n-hexane, and the composite gel is placed in a modification solution for a one-step modification, wherein the modification solution is composed of hexamethyldisilazane and n-hexane in a molar ratio of 1:4;

[0082] Finally, the modified composite gel was pre-frozen for 4 hours and then vacuum freeze-dried at -55°C for 48 hours to obtain a composite material of silica aerogel, basalt fiber and glass fiber, namely, an aerogel-reinforced basalt fiber and glass fiber composite material.

[0083] The thermal conductivity of the aerogel-reinforced basalt fiber and glass fiber composites prepared in the examples was tested to evaluate their thermal insulation properties. Figure 2 As shown, it can be seen that the thermal conductivity values ​​of the three aerogel felts prepared in practice are all low, and the thermal conductivity increases with the increase of the weight ratio of basalt fiber to glass fiber. The three products prepared in the examples were tested for fire resistance. The composite material was wrapped and fixed on the surface of a sling steel wire model with a diameter of 90 mm in an overlapping manner, and then the fireproof sealant and refractory fiber cloth were applied and wrapped on the surface of the composite material in the form of three glues and two cloths. After the sealant was dried, the model was moved into an open flame combustion furnace and a fire resistance test was carried out for 90 minutes at a temperature simulating a HC fire. The surface temperature of the steel wire was as follows: Figure 3 , Figure 4 and Figure 5 It can be seen that the fire-resistant and heat-insulating properties of the composite material are excellent, and the fire-resistant and heat-insulating properties increase with the decrease of the gravity ratio of basalt fiber to glass fiber.

[0084] The present invention and its implementation methods are described above, and such description is not restrictive, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design structures and embodiments similar to the technical solution without creativity, which should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a composite fire-resistant material of aerogel-reinforced basalt fiber and glass fiber for bridges, characterized in that: The following steps are involved: (1) Preparation of basalt fiber and glass fiber composite fiber felt: Firstly, basalt fiber and glass fiber are used as raw materials, and the basalt fiber and glass fiber are cut into short fibers; Then, short-fiber basalt fibers and glass fibers are mixed, and the mixed fibers are pretreated, and then moved into a drum dryer to dry the mixed fibers and obtain uniformly mixed mixed fibers; Finally, the mixed fibers are opened by an opening machine, and then put into a carding machine for fiber combing, and then needle-punched and compacted to obtain a basalt fiber and glass fiber composite fiber mat; (2) Preparation of silica sol: Firstly, tetraethoxysilane, ethanol and water are mixed to prepare a silicon precursor solution; The pH value of the silicon precursor solution is then adjusted with hydrochloric acid; Finally, the mixture of hydrochloric acid and silicon precursor solution is stirred and heated to obtain silica sol; (3) Preparation of aerogel reinforced basalt fiber and glass fiber composites: First, the basalt fiber and glass fiber composite fiber felt prepared in step (1) are immersed in the silica sol prepared in step (2) and placed in a vacuum box; Then, the product is taken out of the vacuum box and the pH value is adjusted with ammonia water to promote the gelation of the silica sol to form a composite gel. After the composite gel is formed, it is placed in ethanol for aging; Then, the water in the composite gel is replaced with n-hexane, and the composite gel is placed in a modification solution for a one-step modification; Finally, the modified composite gel was pre-frozen and then vacuum freeze-dried for 48 hours to obtain a composite material of silica aerogel, basalt fiber and glass fiber.

2. The method for preparing a composite fire-resistant material of aerogel-reinforced basalt fiber and glass fiber for bridges according to claim 1, characterized in that: In step (1), the length of the short fibers is 18-22 mm, and the weight ratio of the short fiber-shaped basalt fibers to the glass fibers is 100-65:0-35.

3. The method for preparing a composite fire-resistant material of aerogel-reinforced basalt fiber and glass fiber for bridges according to claim 1, characterized in that: In step (1), the pretreatment is to use industrial alcohol as a cleaning agent to stir and clean the mixed fibers.

4. The method for preparing a composite fire-resistant material of aerogel-reinforced basalt fiber and glass fiber for bridges according to claim 1, characterized in that: In step (2), tetraethoxysilane, ethanol and water are mixed in a molar ratio of 0.4-0.6:7-9:2.5-3.

5.

5. The method for preparing a composite fire-resistant material of aerogel-reinforced basalt fiber and glass fiber for bridges according to claim 1, characterized in that: In step (2), the pH value of the silicon precursor solution is adjusted to 3-4 with 0.3-0.5 mol / L hydrochloric acid; the mixture of hydrochloric acid and silicon precursor solution is stirred at 38-42° C. and heated for 2 h to obtain silica sol.

6. The method for preparing a composite fire-resistant material of aerogel-reinforced basalt fiber and glass fiber for bridges according to claim 1, characterized in that: In step (3), after the product is taken out from the vacuum box, the pH value is adjusted to 6-7 with 0.4-0.6 mol / L ammonia water.

7. The method for preparing a composite fire-resistant material of aerogel-reinforced basalt fiber and glass fiber for bridges according to claim 1, characterized in that: In step (3), the modified solution is composed of hexamethyldisilazane and n-hexane in a molar ratio of 0.8-1.2:3-5.

8. The method for preparing a composite fire-resistant material of aerogel-reinforced basalt fiber and glass fiber for bridges according to claim 1, characterized in that: In step (3), liquid nitrogen is used for a pre-freezing operation for 4 hours, and the pre-cooled composite gel is vacuum freeze-dried at -60 to -50°C for 48 hours to obtain a composite material of silica aerogel, basalt fiber and glass fiber.

9. The method for preparing a composite fire-resistant material of aerogel-reinforced basalt fiber and glass fiber for bridges according to claim 1, characterized in that: In step (3), after the composite gel is formed, it is placed in ethanol at 38-42° C. for aging for 12 hours.

10. An aerogel-reinforced basalt fiber and glass fiber composite fire-resistant material for bridges prepared by the preparation method according to any one of claims 1 to 9.